Immune-checkpoint inhibitors in melanoma and kidney cancer: from sequencing to rational selection - Michael Flynn; Lisa Pickering; James Larkin; Samra Turajlic (Therapeutic Advances in Medical Oncology, 2018)
Immune-checkpoint inhibitors (ICPIs), including antibodies against cytotoxic T-lymphocyte associated antigen 4 and programmed cell death protein 1, have been shown to induce durable complete responses in a proportion of patients in the first-line and refractory setting in advanced melanoma and renal cell carcinoma. In fact, there are several lines of both targeted agents and ICPI that are now feasible treatment options. However, survival in the metastatic setting continues to be poor and there remains a need for improved therapeutic approaches. In order to enhance patient selection for the most appropriate next line of therapy, better predictive biomarkers of responsiveness will need to be developed in tandem with technologies to identify mechanisms of ICPI resistance. Adaptive, biomarker-driven trials will drive this evolution. The combination of ICPI with specific chemotherapies, targeted therapies and other immuno-oncology (IO) drugs in order to circumvent ICPI resistance and enhance efficacy is discussed. Recent data support the role for both targeted therapies and ICPI in the adjuvant setting of melanoma and targeted therapies in the adjuvant setting for renal cell carcinoma, which may influence the consideration of treatment on subsequent relapse. Approaches to select the optimal treatment sequences for these patients will need to be refined.